Synthesis and morphological study of thick benzyl methacrylate-styrene diblock copolymer brushes - Munirasu, Selvaraj (Langmuir : the ACS journal of surfaces and colloids, 2011)
We demonstrate, for the first time, the synthesis of model poly(benzyl methacrylate) [P(BnMA)] brushes of very high thickness (>300 nm) on silicon wafer. P(BnMA) brush is also synthesized from the surface of silica nanoparticles, from a covalently anchored initiator monolayer, using ambient temperature ATRP. The kinetic studies and block copolymerization from the surface anchored P(BnMA)-Br macroinitiator showed that the polymerization was controlled in nature. AFM, ellipsometry, and water contact angle were used for the characterization of the polymer brush. The grafting density of the P(BnMA) brush, formed by immersion in a dilute monomer solution, was relatively less (∼11% less) in comparison to that obtained by immersion in neat monomer under similar conditions. The P(BnMA)-Br macroinitiator brushes were used to synthesize P(BnMA-b-S) diblock copolymer brushes by the ATRP of styrene at 95 °C. The P(BnMA-b-S) brushes showed stimulus response to a selective solvent and various nanopatterns were observed according to the composition of the block copolymer